2014
DOI: 10.1158/1078-0432.ccr-14-0463
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Synergizes with 34.5ENVE to Enhance Antitumor Efficacy against Metastatic Ovarian Cancer

Abstract: Purpose Novel therapeutic regimens are needed to improve dismal outcomes associated with late-stage ovarian cancer. Oncolytic viruses are currently being tested in patients with ovarian cancer. Here we tested the therapeutic efficacy of combining doxorubicin with 34.5ENVE, an oncolytic herpes simplex virus transcriptionally driven by a modified stem cell-specific nestin promoter, and encoding for anti-angiogenic Vasculostatin-120 (VStat120) for use against progressive ovarian cancer. Experimental Design Anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…All cells were negative for mycoplasma . The construction and generation of 34.5ENVE has been previously described and virus was prepared and titered as previously described (6, 7). Virus was propagated in Vero cells as described (8).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All cells were negative for mycoplasma . The construction and generation of 34.5ENVE has been previously described and virus was prepared and titered as previously described (6, 7). Virus was propagated in Vero cells as described (8).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-four hours later, 0.01 MOI of oHSV was added to the cells. 24 hrs after oHSV infection, 100 ul of Caspase 3/7 substrate was added to the cells for one hour and luminescence was measured by a Fluostar Optima plate reader (BMG Labtech) in triplicate as directed by the manufacturer (7). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment possibilities for breast cancer mainly include radiation therapy, hormone therapy, surgical resection and chemotherapy [3].…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Previous studies have shown combined application of oncolytic HSV-1 along with topoisomerase II inhibitors. 34 This study showed that combined application of a topoisomerase I inhibitor along with oncolytic HSV-1 improves oncolysis in vitro and prolonged the survival of tumor-bearing mice in vivo. Given the repertoire of DNA topoisomerase I functions, all the effects of topoisomerase I inhibition by SN-38 and irinotecan are not entirely ascribed to limited SRSF2 phosphorylation.…”
Section: Discussionmentioning
confidence: 95%